2007
DOI: 10.3354/meps333303
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic larval life of La Réunion ‘bichiques’, amphidromous gobiid post-larvae

Abstract: The 2 amphidromous gobiids Sicyopterus lagocephalus and Cotylopus acutipinnis from La Réunion Island (Mascarene archipelago, south-western Indian Ocean) are heavily exploited by traditional fisheries during their river colonisation. Traits of their oceanic larval life were investigated to better understand the complex life cycle of these fishes. Age estimates were established using otolith increment counts and an alizarin complexon validation method. Larval duration was longer for the widespread S. lagocephalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 16 publications
4
52
0
5
Order By: Relevance
“…Since it was reported that a metamorphosis check (MC) was deposited in their otoliths just after recruitment in S. japonicus, which was accompanied with a change in head morphology (Shen and Tzeng 2002), the presence or absence of a MC was confirmed in the specimens examined. It was tentatively assumed that this species has daily periodicity in the deposition of otolith growth increments, as has been validated in Sicyopterus lagocephalus at Réunion Island (Hoareau et al 2007) and in the sicydiine goby Stiphodon percnopterygionus at Okinawa, Japan (Yamasaki et al 2007). The OLD (here equivalent to age at recruitment) was estimated by counting the otolith increments from the core to the MC for the specimens with a MC (age at metamorphosis) and to the otoliths' edge for those without a MC (total age).…”
Section: Otolith Analysismentioning
confidence: 98%
“…Since it was reported that a metamorphosis check (MC) was deposited in their otoliths just after recruitment in S. japonicus, which was accompanied with a change in head morphology (Shen and Tzeng 2002), the presence or absence of a MC was confirmed in the specimens examined. It was tentatively assumed that this species has daily periodicity in the deposition of otolith growth increments, as has been validated in Sicyopterus lagocephalus at Réunion Island (Hoareau et al 2007) and in the sicydiine goby Stiphodon percnopterygionus at Okinawa, Japan (Yamasaki et al 2007). The OLD (here equivalent to age at recruitment) was estimated by counting the otolith increments from the core to the MC for the specimens with a MC (age at metamorphosis) and to the otoliths' edge for those without a MC (total age).…”
Section: Otolith Analysismentioning
confidence: 98%
“…Other amphidromous species found on oceanic islands have a similarly lengthy PLD (Radtke et al, 2001;Kano, 2006;Hoareau et al, 2007b), an absence of genetic structure across long pelagic distances ( (Myers et al, 2000;Kano and Kase, 2004;Cook et al, 2008). The pelagic larva has only been lost from the life history a few times among the extant freshwater Neritids, and only once in an island species (Holthuis, 1995), even though pelagic larvae have been lost multiple times in other families of marine invertebrates (Duda and Palumbi, 1999;Hart, 2000).…”
Section: The Evolution Of Dispersal In Amphidromous Speciesmentioning
confidence: 99%
“…However, although a community ecologist would view them as freshwater animals (for example, Bandel and Riedel, 1998;Smith et al, 2003), their population ecology may be more similar to that of a marine species, because of their pelagically dispersing larvae. Relatively long pelagic larval durations (PLDs) have been estimated from laboratory cultures of amphidromous gastropod veligers (40-98 days, Holthuis, 1995;Kano, 2006) and the otoliths of amphidromous Galaxiid fishes and gobies (63-266 days, Radtke et al, 1988Radtke et al, , 2001Mcdowall et al, 1994;Hoareau et al, 2007b). These PLDs fall at or above the high end of the range found in the planktotrophic larvae of marine invertebrates (7-293 days, Shanks et al, 2003) and fish (B20-90 days, Brothers et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Studies based on otolith growth estimate the following durations of the oceanic planktonic larval stage: 150 to 169 days for A. guamensis, 119 to 151 days for S. hawaiiensis and 63 to 106 days for L. concolor (Radtke et al, 1988). S. lagocephalus has a planktonic larval stage of 133 to 266 days (Hoareau et al, 2007), allowing its larvae to connect with remote populations and thereby maintain gene flow throughout the 18,000-km wide Indo-Pacific area. These species appear to have high oceanic dependency (Watanabe et al, 2006;Idle et al, 2008).…”
Section: Population Differentiationmentioning
confidence: 99%
“…In amphidromous gobies, dispersal and colonization in remote islands occurs only during the larval planktonic marine phase. The duration of this planktonic stage varies from 133 to 266 days for S. lagocephalus (Hoareau et al, 2007). It is possible that the strength and direction of marine currents and the duration of the planktonic phase together could influence dispersal ability.…”
Section: Introductionmentioning
confidence: 99%